How Millennials Can Promote Social Harmony through Intercultural Communication at Higher Education - Sukardi Weda; Fathu Rahman; Iskandar Abdul Samad; Fahmi Gunawan; Siti Sarah Fitriani (Randwick International of Social Science Journal, 2022)
Intercultural communication is a fundamental key to build social harmony. This study aims to investigate students’ perceptions on promoting social harmony through intercultural communication practices in Indonesia as a multi ethnic and multi culture country. It also investigates the elements that are needed to build social harmony in Indonesia, so that the government of the Republic of Indonesia could take the study report as a reference for formulating policy in social development in Indonesia. This study uses a mix-methods research design (quantitative-qualitative) with a descriptive statistical paradigm that describes the mean, SD, percentage, weight, and rank followed by a detailed explanation of the statements given by the subject. The subjects of this study were students of the Department of English, Faculty of Language and Literature, Universitas Negeri Makassar for the 2019/2020 academic year. The research instrument was a closed and open questionnaire. Therefore, this study indicates that: (1) The results show that several positive behaviors of people from different ethnic groups need to be encouraged, for example tolerance, mutual understanding, mutual respect, not demeaning different tribes, and (2) The results also show that positive stereotypes and inclusive behavior are very important in building social harmony and peace in multi-ethnic countries. The implication of this research is to build social harmony in Indonesia as a multiethnic country that is hampered by hundreds of ethnic groups, cross-cultural competence (CCC) and intercultural communication are very important among Indonesian people, especially for millennials as important elements of social life.